PERBEDAAN PERSEPSI SISWA SMP TERHADAP PEMBELAJARAN MATEMATIKA SECARA DARING DITINJAU DARI GENDER DAN GAYA BELAJAR - Gst Ayu Mahayukti; Pande Putu Gean Ramajaya (UNEJ e-Proceeding, 2022)
This ex post facto study aims to describe and examine the differences in perceptions of public junior high school students in the Klungkung sub-district towards online mathematics learning in terms of gender and student learning styles. This research population is all class VII SMP Negeri students in Klungkung sub-district for the academic year 2021/2022, totaling 1017 students. The sampling technique used is a cluster random sampling technique with a total sample of 124 students. The research instrument used was a questionnaire on learning styles and students' perceptions of online mathematics learning. The instrument used is valid with reliability of 0.721 for the learning style questionnaire and 0.753 for perception. The data were analyzed using the two-way ANOVA and then the Scheffe test. The results showed that: 1) there were differences in students' perceptions of online mathematics learning in terms of gender, and 2) in students' perceptions of online mathematics learning in terms of learning styles. and 3) simultaneously, there are no differences in students' perceptions of online mathematics learning regarding gender and learning styles. With the results of this study, it is hoped that in the future, teachers will no longer differentiate the gender of students and can be more familiar with students' learning styles. This can help teachers provide variations in learning according to the gender and character of students' learning styles. Keywords: gender, learning styles, perceptions, online mathematics learning